Agroindústrias familiares ecológicas e a agregação de valor alimentar: trajetória de mulheres rurais no desenvolvimento regional - Demetrio, Milena (2022)
This research seeks to investigate the addition of food value that occurs in Ecologically Based Family Agroindustrial Systems (SAFEs) with emphasis on the contribution of women's work. SAFEs are an alternative to the hegemonic agrifood system and provide superior quality food, with differentiated attributes, commercialized through short chains and reflecting the food culture of a region. In this context, women's participation is very much linked to sustainable and healthy consumption and production. Despite the great importance of the work that women farmers perform, their efforts are often invisibilized by the social structure that considers their activities as "reproductive" because they do not generate monetary value. Given this scenario, the research asks: how much is the added food value of the ecological family agroindustries in the Southwestern Region of Paraná and what is the role of women farmers in this process? The general objective is to investigate the processes of food value addition in the ecological family agribusinesses in the Southwestern Region of Paraná from the performance of women farmers. The specific objectives are: a) To measure the added value of ecological foods manufactured in family agroindustries of different production and commercialization chains; b) To analyze the trajectory of women in the constitution of ecological family agroindustries; c) To verify the performance of women in the processes of adding value to ecological foods in family agroindustries; and d) To verify if the activities of women farmers, in the ecological family agroindustries, contribute to the transformation of the social gender roles and to their autonomy. For the quantitative stage, we used the economic evaluation method of the productive systems to assess the aggregation of value to the ecological food and the economic participation of women in this process. For the qualitative stage, the topical life history method was used to analyze the trajectory of the women farmers in the construction of the SAFEs and to verify if there are transformations in the social gender roles in the production units. The research is justified by the gap in the literature about the economic participation of women in the aggregation of value to food in ecological family agroindustries. The results of this research demonstrate that agroindustries are an important source of income for these families, with the added value of SAFEs being, on average, R$220,000 per year. Moreover, it was found that women work more hours in the agroindustry, and that there is a large participation of women in commercialization and administrative matters, a fact that demonstrates a trend of transformation of gender roles. However, the productive inclusion of women has not decreased their workload in domestic and care activities, causing them to work a double shift. The research also identified that public purchases are highlighted in the commercialization channels accessed by families, and that digital commerce was encouraged by the Covid19 pandemic, generally being done by women. In this sense, future research can analyze the participation of women farmers in the formation and consolidation of markets, whether digital or physical.